Oxide semiconductor based deep‐subthreshold operated read‐out electronics for all‐printed smart sensor patches - Jyoti Ranjan Pradhan; Sushree Sangita Priyadarsini; Sanjana R. Nibgoor; Manvendra Singh; Subho Dasgupta (Exploration)
Abstract The ability to fabricate an entire smart sensor patch with read‐out electronics using commercial printing techniques may have a wide range of potential applications. Although solution‐processed oxide thin film transistors (TFTs) are capable of providing high mobility electron transport, resulting in large ON‐state current and power output, there is hardly any literature report that uses the printed oxide TFTs at the sensor interfaces. Here, printed amorphous indium‐gallium‐zinc oxide (a‐IGZO)‐based deep‐subthreshold operated TFTs that comprise signal amplifiers and analog‐to‐digital converters (ADCs) that can successfully digitalize the analog sensor signals up to a frequency range of 1 kHz are reported. In addition, exploiting the high current oxide TFTs, a current drive circuit placed after the ADC unit has been found useful in producing easy‐to‐detect visual recognition of the sensor signal at a predefined threshold crossover. Notably, the entire smart sensor patch is demonstrated to operate at a low supply voltage of ≤2 V, thereby ensuring that it can be an on‐chip energy source compatible and standalone detection unit.